Crecimiento y ciclo reproductive de Polymesoda radiata (Bivalvia: Corbiculidae) en Costa Rica - Ruiz Campos, Eleazar (1998)
A populationof green clam, Polymesoda radiata was sampled from August 1992 through July 1993 in Bebedero river, Guanacaste, Costa Rica (n= 978) for demographic data. Mean values (followed by ranges) were: shell length 32.29 ± 7.63 min (6.9-44.10 mm). The mean total weight was 11.13 ± 5.71 g (0.4-23.98 g). Data analysis showed a isometric relationship between Jength and total weight, represente<l by the equatlon: Pt=2.07 x IOALt3.()1 (r=0.987, p< 0:01). Von Bertalanffy’s equations were: for length Lt=45[l _e{-l(t+0.06)(05/2) sen2 «t-065}j and for weight PI;:; 26.53 (1-eH (t + 0.06)]) ,The growth rate for total length was 2.25 ±. 0.66 mm/month for the first year (0.83± 0.24 the second year and 0.26 ±0.1 for other months). Individuals become sexually mature throughout the year. The mean sex ratio was 1.00 male :.0.61 females. Spawning suggested that mínimum size al sexual maturity was 7.80 mm of Lt. The largest number of ripe individuals was found in the dry season. Spawning peaks were in December and March. Histologically this is a dioecious bivalve with stable gonocorism.